2007
DOI: 10.1111/j.1600-0889.2007.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of influences of urban land-use change on ozone distribution over the Pearl River Delta region, China

Abstract: A B S T R A C T Atmospheric dynamical and chemical models are conducted to explore impacts of urban land-use change on ozone concentrations over the Pearl River Delta (PRD) region, China. Two scenarios of land-use distributions are used to represent early 1990s and current urban land-use distributions. Urbanization increases 2-d averaged daytime (nighttime) temperature by 0.8 • C (1.5 • C) and reduces wind speed by about 20% over the PRD urban areas. The daytime boundary layer depth is up to 400 m deeper, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…Nevertheless, it should be noted that, in the daytime, the surface ozone increase (by 2.9%-4.2%) is less than that for the nighttime (about 4.7%-8.5%). This study confirms the finding of Wang et al (2007) that the temperature enhancement and the wind speed decrease alone are not sufficient to explain changes in the surface O 3 concentrations, and the PBL-depth change plays a very important role in surface ozone concentration. At the same time, we found urbanization increases converging over the urban areas, especially in the PRD.…”
Section: Impact Of Urban Expansion On Surface O 3 Concentrationssupporting
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, it should be noted that, in the daytime, the surface ozone increase (by 2.9%-4.2%) is less than that for the nighttime (about 4.7%-8.5%). This study confirms the finding of Wang et al (2007) that the temperature enhancement and the wind speed decrease alone are not sufficient to explain changes in the surface O 3 concentrations, and the PBL-depth change plays a very important role in surface ozone concentration. At the same time, we found urbanization increases converging over the urban areas, especially in the PRD.…”
Section: Impact Of Urban Expansion On Surface O 3 Concentrationssupporting
confidence: 80%
“…The results revealed that air temperature, wind field, humidity, and the height of the atmosphere boundary layer induced by the land-use change (Grossman-Clarke et al, 2005;Liu et al, 2006;Lo et al, 2006;Civerolo et al, 2000;Jiang et al, 2008) can affect the production and distribution of air pollutants (Taha et al, 1998;Civerolo et al, 2007;Wang et al, 2007). In this study, we focused on three parameters: 2-m air temperature, PBL heights, and 10-m wind speed because of their significant roles in the formation and evolution of surface ozone concentrations (Ordonez et al, 2005).…”
Section: Regional Weather-condition Changes Induced By Urban Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of UHII s compares well to the results for other numerical studies. For example, Lee and Kim (2008) found an increase of 1.5 K in the Daegu region in Korea, Wang et al (2007) observed a 1.5 K increase during night time and 0.8 K increased during daytime in the Pearl Delta region, China, and Lamptey et al (2005) found an increase of more than 1 K due to urbanisation in the North-Eastern United States. Results for a case study by Bohnenstengel et al (2011) also suggest a nocturnal urban temperature increment of more than one 1 K in most of the urban area of London.…”
Section: Temperaturementioning
confidence: 99%
“…surfaces to artificial ones (Civerolo et al, 2007;Lo et al, 2007;Wang et al, 2007;Jiang et al, 2008;Lu et al, 2010;Wu et al, 2011;Chen et al, 2014b;Liao et al, 2015;Zhu et al, 2015;Li et al, 2016) and the release of anthropogenic heat from human activities in cities (Ryu et al, 2013;Yu et al, 2014;Xie et al, 2016). Anthropogenic heat (AH) can increase turbulent fluxes in sensible and latent heat (Oke, 1988), implying that it can modulate local and regional meteorological processes (Ichinose et al, 1999;Block et al, 2004;Fan and Sailor, 2005;Ferguson and Woodbury, 2007;Zhu et al, 2010;Feng et al, 2012Feng et al, , 2014Menberg et al, 2013;Ryu et al, 2013;Wu and Yang, 2013;Bohnenstengel et al, 2014;Chen et al, 2014a;Meng et al, 2011;Yu et al, 2014;Xie et al, 2016) and thereby exert an important influence on the formation and the distribution of ozone (Ryu et al, 2013;Yu et al, 2014;Xie et al, 2016) as well as aerosols (Yu et al, 2014;Xie et al, 2016).…”
mentioning
confidence: 99%